Design of rotor for internal batch mixer and mixing elements for twin screw extruder for polyolefin processing - Salahudeen, Shafaat Ahmed (2017)
Mixing is the key component of polymer processing to achieve homogeneity of final product. Previous researchers have reported poor mixing performance of internal batch mixer (IBM) and twin screw extruder (TSE) due to improper distributive and dispersive mixings. This leads to poor product properties. Hence to overcome the problem, this research aims to design a rotor and mixing element to improve mixing performance of IBM and TSE. The basic rotor design for IBM was developed on the concept of Banbury and roller rotors and this design was then optimized to attain secondary flow. Distributive mixing performance of the optimized rotor was compared with commercial rotors using ANSYS Polyflow, with results showing the new rotor was found to be better than commercial rotors. Based on these results, a prototype of optimized design rotor was developed using Computer Numerical Control machine. Using this prototype rotor, nano calcium carbonate was dispersed in high density polyethylene and its morphology was analysed via scanning electron microscopy (SEM). SEM results showed improved dispersive mixing performance of prototype rotor compared to that of commercial rotor. This prototype rotor design was later modified into two mixing elements namely, Bean-UTM for intermeshing co-rotating TSE and Blade-UTM for intermeshing counter-rotating TSE. The Bean-UTM and Blade-UTM were examined for dispersive mixing (mixing index) and distributive mixing (logarithm of length of stretch, instantaneous efficiency and time average efficiency) and then were compared with commercial TSE mixing elements. The results showed Bean-UTM has better mixing performance than kneader mixing element of Dr. Collin TSE and the Blade-UTM has better mixing performance than screw mixing element of Coperian TSE. The findings of this research will hopefully solve the issue of poor mixing in IBM and TSE.